An Annotated Checklist of the Vascular Flora of Coastal Mangrove Ecosystems of Barguna District, Bangladesh - Islam, Md Rafiqul; Hossain, Gazi Mosharof; Rahman, Mohammad Mahfuzur (Bangladesh Journal of Plant Taxonomy, 2022)
This study provides the basic taxonomic data on the vascular flora of the coastal mangrove ecosystems in Barguna district of Bangladesh. Plant samples and field data have been collected following walk through method. The present study reveals the occurrence of 532 species under 378 genera and 112 families in the study area, of which 24 are true mangroves, 46 mangrove associates and 461 non-mangroves. The pteridophytes are composed of 22 species under 20 genera of 12 families and gymnosperms of two species under two genera and two families. Magnoliopsida are composed of 375 species under 279 genera and 77 families, and Liliopsida of 133 species belonging to 77 genera under 21 families. Fabaceae with 28 species is recorded as the largest dicot family, followed by Asteraceae, Apocynaceae, Euphorbiaceae and Malvaceae. Poaceae with 45 species is the largest monocot family, followed by Cyperaceae, Araceae and Arecaceae. About 60.15% of these species are herbs, 21.80% trees, 15.79% shrubs, 1.88% palms and 0.38% bamboos. The study area composed with 74.06% native and 25.94% exotic species, 79.70% species are wild, 16.35% planted and 3.95% cultivated species. Majority of the species are found to grow in forest margin, roadside, woodland, wetland and river bank. Most of the species are economically useful as medicine, ornamental and vegetable. This study concludes that the floristic composition of coastal mangrove ecosystems of Barguna district is still rich though the area facing some severe threats. This study strongly recommends adopting effective master plan and implementing adequate measures for sustainable conservation and monitoring of the biodiversity of this disaster-prone area. Bangladesh J. Plant Taxon. 29(2): 403-429, 2022 (December)